Endocervical Adenocarcinoma With Skip Lesion in a Fundal Endometrial Polyp Mimicking Endometrioid Adenocarcinoma Arising From Endometrial Polyp. (11th September 2019) - Aakash, Nfn; Murzabdillaeva, Albina; Lin, Mei; Zhang, Songlin
Abstract: Human papillomavirus–related adenocarcinomas account for approximately 20% of all cervical cancers. Most of them arise in the transformation zone but may be found exclusively in endocervical canal. Contiguous spread into the lower uterine segment is known to occur, but finding a "skip" lesion in a fundal endometrial polyp poses an interesting pathologic conundrum. We present a case of a 57-year-old woman with a history of postcoital bleeding and abnormal cervical smear. Cervical exam showed a 2-cm exophytic mass on anterior cervix. Biopsy revealed invasive endocervical adenocarcinoma. Patient underwent radical hysterectomy. Gross examination revealed large cervical mass without involvement of low uterine segment and a benign-appearing small uterine fundal polyp. Microscopic examination confirmed the deeply invasive endocervical adenocarcinoma, and the benign-appearing endometrial polyp had similar atypical glands on the polyp surface and admixed with benign endometrial glands. Both cervical tumor and the carcinoma involving endometrial polyp demonstrated identical immunohistochemistry showing diffuse positive p16 and CEA(m) and negative for ER and vimentin. The authors report a rare case of endocervical adenocarcinoma with skip lesion in the endometrial fundal polyp, and rare cases with skip lesion in the fallopian tubes from endocervical adenocarcinoma have been reported in the literature. High clinical suspicion and ancillary immunohistochemistry are necessary to differentiate the lesion from endometrioid or papillary carcinoma arising from endometrial polyp.